Subtle Evasions: Mary Sidney and Social Expectations for Women’s Private Roles - Diede, Martha (2013)
Like never before, women and men have public personas, and the actions of the private person have consequences for the public person. The advent of MySpace,Facebook, and Google+, for example, has given every member a public persona that masquerades as a private one, although it is easily searchable in a few seconds with an internet connection. Much like Early Modern commonplace books in which people wrote down quotes they found particularly applicable to their lives or recorded small and large life events, Facebook and similar social networking sites serve as a record of daily activities, thoughts, and sometimes quotes for individual members. Then, as now, those women whose lives cannot be fully chronicled by social media, find that the news networks may take up the slack. Unlike the commonplace book and other private literary pieces that women then wrote for themselves or to circulate among trusted friends, social media now brings with it an inherent danger of public overexposure, an online reputation that anyone can find with an internet connection. The Early Modern woman called her pre-electronic version of this problem publicity. Just as today's smart users care about the degree to which unsavory users can access their information and what they post online,smart women and men in Elizabethan England took great care to maintain their good public reputations. Although Elizabethan society allowed men to have public lives while preserving their private lives at country houses or simply at home in the city, that same society dictated that women avoid public life as much as possible.